2015
DOI: 10.4034/pboci.2015.151.07
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Posterior Cross Bite in 3-5-Year-Old Children from Vitória, Brazil

Abstract: Objective: To evaluate the prevalence of posterior cross bite and the possible association with deleterious oral habits in 3-5-year-old children from Vitória, Espírito Santo, Brazil. Material and Methods: This retrospective observational study with a longitudinal design used as parameters for sample calculation prevalence of 35%, confidence level of 95% and error of 5%. The final random sample included 903 children, proportionally distributed according to the number of children enrolled per school. Thus, the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…In addition to that thumb sucking habit appeared to increase possibility of developing such malocclusion by 40 folds. This study concluded that there is no statistical difference between the cases group and controls group in the occurrence of posterior cross bite this result in accordance with Singh et al and Miotto et al (12,22) but, disagree with results of previously conducted studies (27,30) who found that the posterior cross bite had been observed to directly associated with oral habits The adjusted odds ratio for posterior cross bite was giving an indication that thumb sucking habit was a risk factor and increasing 3 times the likelihood of the development of posterior cross bite. From comparing the occurrence of malocclusions in cases group only the study showed that the frequencies of malocclusion are not age related neither gender related as there is no statistical difference among age and gender groups in the occurrence of malocclusions attributed to the oral habit this agree with Adair study (31).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In addition to that thumb sucking habit appeared to increase possibility of developing such malocclusion by 40 folds. This study concluded that there is no statistical difference between the cases group and controls group in the occurrence of posterior cross bite this result in accordance with Singh et al and Miotto et al (12,22) but, disagree with results of previously conducted studies (27,30) who found that the posterior cross bite had been observed to directly associated with oral habits The adjusted odds ratio for posterior cross bite was giving an indication that thumb sucking habit was a risk factor and increasing 3 times the likelihood of the development of posterior cross bite. From comparing the occurrence of malocclusions in cases group only the study showed that the frequencies of malocclusion are not age related neither gender related as there is no statistical difference among age and gender groups in the occurrence of malocclusions attributed to the oral habit this agree with Adair study (31).…”
Section: Discussionsupporting
confidence: 87%
“…A previously conducted studies mentioned that posterior cross bite attributed to dummy sucking habit rather than thumb sucking habit (8,11,(20)(21)(22) . The harmful effect of thumb sucking habit on development of occlusion was found to be the main reason behind mothers attempts to stop this habit in their children (23) .…”
Section: Introductionmentioning
confidence: 99%